Nucleosome landscape reflects phenotypic differences in Trypanosoma cruzi life forms. - Alex R J Lima; Christiane B de Araujo; Saloe Bispo; José Patané; Ariel M Silber; M Carolina Elias; Julia P C da Cunha (PLoS Pathogens)
Trypanosoma cruzi alternates between replicative and nonreplicative life forms, accompanied by a shift in global transcription levels and by changes in the nuclear architecture, the chromatin proteome and histone posttranslational modifications. To gain further insights into the epigenetic regulation that accompanies life form changes, we performed genome-wide high-resolution nucleosome mapping using two T. cruzi life forms (epimastigotes and cellular trypomastigotes). By combining a powerful pipeline that allowed us to faithfully compare nucleosome positioning and occupancy, more than 125 thousand nucleosomes were mapped, and approximately 20% of them differed between replicative and nonreplicative forms. The nonreplicative forms have less dynamic nucleosomes, possibly reflecting their lower global transcription levels and DNA replication arrest. However, dynamic nucleosomes are enriched at nonreplicative regulatory transcription initiation regions and at multigenic family members, which are associated with infective-stage and virulence factors. Strikingly, dynamic nucleosome regions are associated with GO terms related to nuclear division, translation, gene regulation and metabolism and, notably, associated with transcripts with different expression levels among life forms. Finally, the nucleosome landscape reflects the steady-state transcription expression: more abundant genes have a more deeply nucleosome-depleted region at putative 5' splice sites, likely associated with trans-splicing efficiency. Taken together, our results indicate that chromatin architecture, defined primarily by nucleosome positioning and occupancy, reflects the phenotypic differences found among T. cruzi life forms despite the lack of a canonical transcriptional control context.